Direct Conversion of Syngas into Methyl Acetate, Ethanol, and Ethylene by Relay Catalysis via the Intermediate Dimethyl Ether. (14th August 2018) - Zhou, Wei; Kang, Jincan; Cheng, Kang; He, Shun; Shi, Jiaqing; Zhou, Cheng; Zhang, Qinghong; Chen, Junchao; Peng, Luming; Chen, Mingshu; Wang, Ye
Abstract: Selective conversion of syngas (CO/H2 ) into C2+ oxygenates is a highly attractive but challenging target. Herein, we report the direct conversion of syngas into methyl acetate (MA) by relay catalysis. MA can be formed at a lower temperature (ca. 473 K) using Cu‐Zn‐Al oxide/H‐ZSM‐5 and zeolite mordenite (H‐MOR) catalysts separated by quartz wool (denoted as Cu‐Zn‐Al/H‐ZSM‐5|H‐MOR) and also at higher temperatures (603–643 K) without significant deactivation using spinel‐structured ZnAl2 O4 |H‐MOR. The selectivity of MA and acetic acid (AA) reaches 87 % at a CO conversion of 11 % at 643 K. Dimethyl ether (DME) is the key intermediate and the carbonylation of DME results in MA with high selectivity. We found that the relay catalysis using ZnAl2 O4 |H‐MOR|ZnAl2 O4 gives ethanol as the major product, while ethylene is formed with a layer‐by‐layer ZnAl2 O4 |H‐MOR|ZnAl2 O4 |H‐MOR combination. Close proximity between ZnAl2 O4 and H‐MOR increases ethylene selectivity to 65 %.